Erythrocyte apoptosis (erythroptosis) and anaemia in chronic HIV-1 infection : relationship with immune activation and viraemia - Loots, Stanley (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScMedSc)-- Stellenbosch University, 2013.